1996
DOI: 10.1074/jbc.271.21.12585
|View full text |Cite
|
Sign up to set email alerts
|

The Predominant Protein-arginine Methyltransferase from Saccharomyces cerevisiae

Abstract: We have identified the major enzymatic activity responsible for the S-adenosyl-L-methionine-dependent methylation of arginine residues (EC 2.1. Evidence for the posttranslational methylation of arginine residues in proteins was first provided by the presence of radioactive species chromatographing at positions near that of arginine in acid hydrolysates of isolated calf thymus nuclei incubated with S-adenosyl-L- [methyl-14

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
237
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(261 citation statements)
references
References 67 publications
7
237
0
Order By: Relevance
“…Sedimentation profile of ZZ-Rrp8p, Gar1p, and large subunit ribosomal protein rpL3 on a glycerol gradient+ A total extract from strain JG590 (expressing ZZ-Rrp8p) was loaded on a 10-30% glycerol gradient and subjected to centrifugation+ Fractions were collected [numbered from 1 (top of the gradient) to 20 (bottom of the gradient)] and proteins in each fraction were precipitated with TCA, separated by SDS-PAGE, and revealed by western blotting+ Fractions containing the peak of 40S, 60S, and 80S ribosomal subunits are indicated by arrows+ which guide RNAs have been identified+ Although we deem it unlikely, the possibility remains that Rrp8p introduces some of the four 29O-ribose methylations that are unaccounted for, in particular the methylation of adenine 436 in 18S rRNA (Lowe & Eddy, 1999)+ Aside from 29-O ribose methylations, rRNAs undergo base methylations which are thought to be added by specific protein enzymes+ The only well-characterized eukaryotic rRNA base modification enzyme is Dim1p, responsible for the dimethylation of two consecutive adenines in 18S and also required for 18S rRNA synthesis (Lafontaine et al+, 1995; Lafontaine & Tollervey, 1998)+ In addition, it is likely that the nucleolar protein Nop2p, necessary for proper 27S pre-rRNA processing (Hong et al+, 1997), is a m 5 C-methyltransferase modifying rRNA (Motorin & Grosjean, 1999)+ No evidence so far allows us to exclude the possibility that Rrp8p could catalyze one or several rRNA base methylations+ Another possibility is that Rrp8p catalyzes the arginine methylation of nucleolar proteins+ Indeed it has been demonstrated that the arginine found in the FGGRGGF sequence present several times in the GAR domain is modified to asymmetric N G , N G dimethylarginine (asymmetric DMA)+ DMA can be detected FIGURE 10. Analysis of snRNAs and proteins associated with ZZ-Rrp8p+ A: Patterns of 39-end-labeled snRNAs associated with ZZ-Rrp8p+ Yeast extracts were produced from cells expressing ZZ-Nop1p (lanes 1 and 2), Gar1p-ZZ (lanes 3 and 4), or ZZ-Rrp8p (lanes 5 and 6)+ RNAs purified from the total extracts (T, lanes 1, 3, 5) or from the pellets obtained after immunoprecipitations performed in 200 mM KAc using IgG-sepharose (P, lanes 2, 4, 6) were 39 end-labeled with [ 32 P]pCp and separated on a 6% sequencing gel+ Positions of some of the C/D and H/ACA snoRNAs inferred from their size are indicated+ M: molecular weight markers (pBR322 digested with HaeIII/TaqI)+ B: Northern analysis of immunoprecipitated RNAs+ RNAs purified from pellets obtained following immunoprecipitation of Gar1p-ZZ (lane 1), ZZ-Nop1p (lane 2), or ZZ-Rrp8p from cellular extracts were separated by PAGE, transferred onto a nylon membrane, and hybridized with antisense oligodeoxynucleotide probes detecting snR10, snR42, and snR190+ C: Western analysis of proteins associated with ZZ-Rrp8p+ To attempt to characterize proteins associated with ZZ-Rrp8p, a total cellular extract from strain JG590 expressing ZZ-Rrp8p was produced using a 200-mM KAc buffer+ This extract was subjected to IgG-sepharose chromatography+ Proteins from 1/100 of total lysate (Start), 1/100 of unbound fraction (Unbound), and 1/20 of eluted fraction (Eluate) were precipitated using TCA, separated by SDS-PAGE and analyzed by western blotting+ Antibodies against U3-associated proteins (Mopp10p, Lcp5p, and Nop1p), H/ACA snoRNP proteins (Gar1p and Nhp2p), C/D snoRNP protein (Nop1p), or the nucleolar GAR domain-containing protein Nsr1p were used+ on the GAR domains of the S. cerevisiae hnRNP proteins A1, Npl3p, and Hrp1p and of the nucleolar proteins Nop1p (fibrillarin), Gar1p, and Nsr1p (Gary et al+, 1996)+ ...…”
Section: Discussionmentioning
confidence: 99%
“…Sedimentation profile of ZZ-Rrp8p, Gar1p, and large subunit ribosomal protein rpL3 on a glycerol gradient+ A total extract from strain JG590 (expressing ZZ-Rrp8p) was loaded on a 10-30% glycerol gradient and subjected to centrifugation+ Fractions were collected [numbered from 1 (top of the gradient) to 20 (bottom of the gradient)] and proteins in each fraction were precipitated with TCA, separated by SDS-PAGE, and revealed by western blotting+ Fractions containing the peak of 40S, 60S, and 80S ribosomal subunits are indicated by arrows+ which guide RNAs have been identified+ Although we deem it unlikely, the possibility remains that Rrp8p introduces some of the four 29O-ribose methylations that are unaccounted for, in particular the methylation of adenine 436 in 18S rRNA (Lowe & Eddy, 1999)+ Aside from 29-O ribose methylations, rRNAs undergo base methylations which are thought to be added by specific protein enzymes+ The only well-characterized eukaryotic rRNA base modification enzyme is Dim1p, responsible for the dimethylation of two consecutive adenines in 18S and also required for 18S rRNA synthesis (Lafontaine et al+, 1995; Lafontaine & Tollervey, 1998)+ In addition, it is likely that the nucleolar protein Nop2p, necessary for proper 27S pre-rRNA processing (Hong et al+, 1997), is a m 5 C-methyltransferase modifying rRNA (Motorin & Grosjean, 1999)+ No evidence so far allows us to exclude the possibility that Rrp8p could catalyze one or several rRNA base methylations+ Another possibility is that Rrp8p catalyzes the arginine methylation of nucleolar proteins+ Indeed it has been demonstrated that the arginine found in the FGGRGGF sequence present several times in the GAR domain is modified to asymmetric N G , N G dimethylarginine (asymmetric DMA)+ DMA can be detected FIGURE 10. Analysis of snRNAs and proteins associated with ZZ-Rrp8p+ A: Patterns of 39-end-labeled snRNAs associated with ZZ-Rrp8p+ Yeast extracts were produced from cells expressing ZZ-Nop1p (lanes 1 and 2), Gar1p-ZZ (lanes 3 and 4), or ZZ-Rrp8p (lanes 5 and 6)+ RNAs purified from the total extracts (T, lanes 1, 3, 5) or from the pellets obtained after immunoprecipitations performed in 200 mM KAc using IgG-sepharose (P, lanes 2, 4, 6) were 39 end-labeled with [ 32 P]pCp and separated on a 6% sequencing gel+ Positions of some of the C/D and H/ACA snoRNAs inferred from their size are indicated+ M: molecular weight markers (pBR322 digested with HaeIII/TaqI)+ B: Northern analysis of immunoprecipitated RNAs+ RNAs purified from pellets obtained following immunoprecipitation of Gar1p-ZZ (lane 1), ZZ-Nop1p (lane 2), or ZZ-Rrp8p from cellular extracts were separated by PAGE, transferred onto a nylon membrane, and hybridized with antisense oligodeoxynucleotide probes detecting snR10, snR42, and snR190+ C: Western analysis of proteins associated with ZZ-Rrp8p+ To attempt to characterize proteins associated with ZZ-Rrp8p, a total cellular extract from strain JG590 expressing ZZ-Rrp8p was produced using a 200-mM KAc buffer+ This extract was subjected to IgG-sepharose chromatography+ Proteins from 1/100 of total lysate (Start), 1/100 of unbound fraction (Unbound), and 1/20 of eluted fraction (Eluate) were precipitated using TCA, separated by SDS-PAGE and analyzed by western blotting+ Antibodies against U3-associated proteins (Mopp10p, Lcp5p, and Nop1p), H/ACA snoRNP proteins (Gar1p and Nhp2p), C/D snoRNP protein (Nop1p), or the nucleolar GAR domain-containing protein Nsr1p were used+ on the GAR domains of the S. cerevisiae hnRNP proteins A1, Npl3p, and Hrp1p and of the nucleolar proteins Nop1p (fibrillarin), Gar1p, and Nsr1p (Gary et al+, 1996)+ ...…”
Section: Discussionmentioning
confidence: 99%
“…3). Currently, only four PRMTs have been identified in yeast and it appears that Rmt1 (Hmt1) is the predominant arginine methyltransferase, because cells that lack Rmt1 show a significant reduction in asymmetric monomehtylation and dimethylation (Gary et al, 1996). Yeast cells also have the only type III PRMT, Rmt2, whereas Hsl7 and Skb1 represent type II PRMT in S. cerevisiae and S. pombe, respectively (Zobel-Thropp et al, 1998;Ma, 2000).…”
Section: Protein Arginine Methyltransferasesmentioning
confidence: 99%
“…In S. cerevisiae, there are two established orthologs of the PRMT1-9 family -Rmt1 (mammalian PRMT1 ortholog; (85) and Hsl7 (mammalian PRMT5 ortholog; Ref. 86).…”
Section: An Unusual Protein Arginine Methyltransferase That Modifies mentioning
confidence: 99%